2016
DOI: 10.1002/msc.1160
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Pharmacist‐Led Collaborative Follow‐Up Care in an Ambulatory Rheumatology Clinic

Abstract: A collaborative care model can exceed the already high expectations for care of patients with inflammatory arthritis. Our findings support the role of pharmacists using a collaborative care approach to care for patients in rheumatology clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Findings of this review were consistent with those previously reported by Alhusein and Watson [28]. It is probably important for future studies to include patients as panelists who can actively participate in the voting process and selection of the consensus-based quality indicators because patients are the clientele and, in many healthcare systems, satisfaction of the clientele has been considered a high priority [72,73]. It is noteworthy mentioning that priorities might change with time and hence quality indicators might need to be revisited periodically to keep up with changes in priorities and evolution of roles and services that could be played by pharmacists [40][41][42].…”
Section: Discussionsupporting
confidence: 85%
“…Findings of this review were consistent with those previously reported by Alhusein and Watson [28]. It is probably important for future studies to include patients as panelists who can actively participate in the voting process and selection of the consensus-based quality indicators because patients are the clientele and, in many healthcare systems, satisfaction of the clientele has been considered a high priority [72,73]. It is noteworthy mentioning that priorities might change with time and hence quality indicators might need to be revisited periodically to keep up with changes in priorities and evolution of roles and services that could be played by pharmacists [40][41][42].…”
Section: Discussionsupporting
confidence: 85%
“…Acceptance of pharmacists’ extended roles by physicians and other health care workers has produced significant positive outcomes in patient care in these countries [ 59 , 60 ]. The numerous interventions in medication management reported in these countries demonstrate the high level of trust of pharmacists by the general public in these countries [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction was not significantly different according to age, gender, ethnicity or number of disease states but, satisfaction with the medication therapy management correlated positively with overall patient satisfaction. Hall  et al 14 described and compared patient satisfaction with two different types of care: a pharmacist physician collaborative model and a traditional physician model in a rheumatology clinic setting. Patient satisfaction in the collaborative care group was consistently higher across all dimensions.…”
Section: Discussionmentioning
confidence: 99%